A controlled study of the influence of comorbidity on activities of daily living in elderly cancer survivors (the HUNT-3 survey). Issue 5 (September 2017) - Grov, Ellen Karine; Fosså, Sophie D.; Dahl, Alv A.
Abstract: Objectives: To examine the influence of somatic comorbidity on Activity of Daily Living (ADL) problems in cancer survivors ≥ 70 years (ECSs) based on data from The Health Study of Nord-Trøndelag County (HUNT-3) 2006–08. Material and Methods: Among participants of the HUNT-3 survey, 599 ECSs had a diagnosis of one invasive cancer according to both The Cancer Registry of Norway and self-report. Three controls without cancer aged ≥ 70 years for each ECS were drawn from the HUNT-3 sample. We compared personal-ADL (P-ADL) and instrumental-ADL (I-ADL) problems for ECSs and differences between ADL problems for ECSs with and without comorbidity and controls with and without comorbidity. Results: The prevalence of P-ADL problems was 3.5% among ECSs and 2.9% among controls (p = 0.97) and for I-ADL 28.5% versus 21.4% (p = 0.01), respectively. In bivariate analyses where ECSs versus controls was the dependent variable, presence of I-ADL problems, higher age, being female, paired relationship, poor self-rated health, hospitalization last year, and low level of neuroticism were associated being ECSs. In multivariate analyses, these variables, except I-ADL-problems and paired relationship, remained significantly associated being ECSs. No significant differences were shown for P-ADL problems when comparing ECSs and controls with comorbidity, and ECSs with and without comorbidity. ECSs with comorbidity reported significantly more I-ADL-problems than controls with comorbidity, and ECSs with comorbidity had significantly more I-ADL-problems than ECSs without comorbidity. Conclusion: Our results reflect common factors found in ADL studies in the elderly population. Health personnel have to be particularly observant on I-ADL problems among female ECSs, and those reporting poor self-rated health or comorbidity.